FAO's statistic data and sustainability of fisheries and aquaculture: Comments on Pauly and Zeller (2017). (July 2017) - Ye, Yimin; Barange, Manuel; Beveridge, Malcolm; Garibaldi, Luca; Gutierrez, Nicolas; Anganuzzi, Alejandro; Taconet, Marc
Abstract: In a recent commentary, Pauly and Zeller disagreed with the Food and Agriculture Organization's interpretation of its global capture fishery production records, arguing that trends were distorted by unreliable statistics in some countries. They criticized FAO for not having used their "catch reconstructions" in the 2016 State of the World Fisheries and Aquaculture (SOFIA) report and questioned the interpretation and significance of FAO's aquaculture production statistics. In this paper, we refute their claims and demonstrate that their critique is based on fundamental misunderstandings caused by mixing up statistical metrics and using simple normative explanations to interpret highly complex datasets. We explain how FAO maintains, curates and updates the only validated source of global fisheries landings, describe our capacity building projects and activities underpinning the annual updates for the over 231 different sources of fisheries data, and clarify such updates include dialogues with member countries to improve and revise present and historical records. FAO will continue to work closely with member states, IGOs, NGOs, academia and civil society, to further improve fishery and aquaculture databases, while calling on states to make renewed efforts to improve data quality. It also welcomes research efforts that contribute to the improvement of statistical data which are critical to the sustainable management of fisheries and aquaculture.